Kebijakan Investasi Eco City di Rempang dan Implikasinya Terhadap Ekonomi Masyarakat dengan Perspektif Ekonomi Islam - Rafiqoh Lubis, Nurul; Ridwan, M; Batubara, Maryam (Universitas Hamzanwadi, 2024)
This study is set against the backdrop of the Eco City Investment Policy implementation in Rempang, which is a sustainable urban development strategy aiming to integrate economic growth with environmental preservation. The primary objective of this research is to analyze the impact of the Eco City Investment Policy on the local community's economy from an Islamic Economics perspective, emphasizing social-economic balance and justice, as well as environmental preservation. The research methodology is qualitative, utilizing a descriptive approach to collect and analyze data obtained from secondary sources. The findings indicate that the Eco City Investment Policy in Rempang has significant potential to enhance community welfare through job creation and increased environmental awareness, in line with the Islamic economic principle of balance and justice. However, there are challenges and obstacles in its implementation, requiring commitment and coordination among stakeholders. The implication of this research is the necessity to incorporate Islamic Economic values and principles in the planning and implementation of sustainable development policies like Eco City, to achieve fair and sustainable economic growth in harmony with the environment. This study contributes to the understanding of how sustainable investment policies can be designed and implemented to support inclusive and environmentally friendly economic growth in accordance with Islamic Economic principles.